Hydrocolloids effect on coating batter and on organoleptic properties of rissol regenerated in oven and comparison with deep-frying process - Ana Patricia Sousa; Manuela Vaz Velho; Manuel Alves; Rita Pinheiro (Millenium, 2019)
Introduction: Consumers' preference for lower fat products continues to increase and there is a significant pressure on industry to reduce the use of frying processes.